Milk Intake Enhances Cerebral Antioxidant (Glutathione) Concentration in Older Adults: A Randomized Controlled Intervention Study. (7th June 2021) - Choi, In-Young; Taylor, Matthew; Lee, Phil; Alhayek, Sibelle Alwatchi; Bechetel, Misty; Hamilton-Reeves, Jill; Spaeth, Kendra; Adany, Peter; Sullivan, Debra
Abstract: Objectives: This randomized controlled trial was to confirm the potential benefit of adequate dairy food intake to raise brain antioxidant, glutathione (GSH), in low dairy consumers through a longitudinal dietary intervention. This confirmatory study is based on our previous findings of positive correlations between brain GSH levels and dairy food consumption, particularly milk ( P < 0.001), in a cross-sectional study of older adults. Methods: A total of 80 older adults with a low dairy intake (≤1.5 servings/day) were enrolled in a 3-month milk intervention study. Brain GSH levels were measured using multiple quantum chemical shift imaging at 3 T. After baseline MR scans, participants were randomized into either the intervention or control group using a random-sequence algorithm. The control group continued their usual intake of dairy ≤1.5 servings/day (<1 cup of milk/day) while the milk intervention group was provided 1% milk weekly and instructed to consume 3 cups of milk/day for three months. Dietary intake was assessed with 24-hr diet recalls, 7-day food records, and a Diet Screener Questionnaire and was analyzed using NDSR software. Brain GSH levels in each group were compared between baseline and post-intervention using paired t-tests, and longitudinal changes of GSH levels were compared between groups using two sample t-tests. Results: Among 80 enrolled participants (60–89 years old), 66 participants (49 intervention; 17 controls) completed the study. The milk intake of the controls was similar at baseline and the end of study timepoints (0.4 ± 0.4 cups/day for both), while that of the intervention group increased from 0.2 ± 0.3 cups/day to 3.0 ± 0.6 cups/day ( P < 0.001). The intervention group showed 7.4 ± 11.7% increases in parietal GSH ( P < 0.001) and 4.6 ± 8.7% increases in fronto-parietal GSH ( P = 0.003) levels after intervention, while the control group showed no changes in brain GSH. The fronto-parietal GSH increase in the intervention group was greater than that of the control group ( P < 0.05). Conclusions: Dietary milk consumption could modulate brain GSH levels. This study demonstrates the effect of diet on brain antioxidants, which could lead to the development of new strategies in strengthening cerebral antioxidant defenses and thereby improving brain health in the aging population. Funding Sources: National Dairy Council.